The Mediating Role of Work–Life Balance in Improving Employee Well-Being - Ravindra Reksinosa; Sri Wartini (Management Analysis Journal, 2024)
This study research aims to examine work-life balance in mediating the effect of work flexibility on employee well-being. Well-being is an important factor in maintaining human resources in an organization. The sample for this study consisted of 102 employees of the Kebumen Regency Land Office. The sampling technique used was saturated sampling, in which the entire population was sampled and analyzed using SmartPLS 3.0. The direct test results showed that work flexibility had no effect on employee well-being, while work-life balance had an effect on employee well-being. Indirect testing showed that work-life balance could mediate the relationship between work flexibility and employee well-being. Suggestions for further research include developing other independent variables such as leadership, motivation, self-efficacy, and organizational culture.